SISTEM PENGUKUR TINGGI DAN BERAT BADAN UNTUK POSYANDU MENGGUNAKAN MIKROKONTROLER ATmega8535 - Hendra Kusumah; Alfian toro; Muhamad Idris (CCIT Journal, 2016)
Height and weight gauge on posyandu ussually doing at the time of immunization healt checking. But the tools are used still it manually and separately, accuracy is also one of the problem in terms of the measurement. Then for fix the issue should be made a system for measuring height and weight are computerized. This system can be build by harness Microcontroller ATmega8535 as a system controller. Ultrasonic PING sensor as a toddler height gauge. Strain gauge sensors as a toddler weight gauge. To convert the analog signal into digital using IC ADC 0804, LCD and 16x2 as its output